2017
DOI: 10.1186/s13722-017-0100-2
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of screening and brief intervention for unhealthy alcohol use in an urban academic Federally Qualified Health Center

Abstract: BackgroundScreening and brief intervention (SBI) for unhealthy drinking has not been widely implemented in primary care partly due to reliance on physicians to perform it.MethodsWe implemented a model of nursing staff-delivered SBI for unhealthy drinking for adult patients receiving primary care at an academically-affiliated Federally Qualified Health Center in the Bronx, NY. Our model consisted of nursing staff screening all patients with the alcohol use disorders identification test consumption questions (AU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…These prevention interventions were often tailored for ethnic and cultural differences, values, beliefs and practices (Connolly et al, 2017 ; Crowley et al, 2013 ; Gary et al, 2009 ; Weiler & Tirrell, 2007 ). For instance, studies featured community healthcare workers (CHWs) with the same ethnicity as patients (Allen et al, 2011 ; Brown et al, 2011 ; El Fakiri et al, 2008 ; Gary et al, 2009 ; Jansen et al, 2007 ), interventions using patients' native language(s) (Choi & Rush, 2012 ; Piñeiro et al, 2020 ) and bilingual nurses (Bachhuber et al, 2017 ; Brown et al, 2011 ; Choi & Rush, 2012 ; Weiler & Tirrell, 2007 ). Traditional beliefs in relation to medical practice were also acknowledged (Choi & Rush, 2012 ), and culturally appropriate foods were recommended (Brown et al, 2011 ; Choi & Rush, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These prevention interventions were often tailored for ethnic and cultural differences, values, beliefs and practices (Connolly et al, 2017 ; Crowley et al, 2013 ; Gary et al, 2009 ; Weiler & Tirrell, 2007 ). For instance, studies featured community healthcare workers (CHWs) with the same ethnicity as patients (Allen et al, 2011 ; Brown et al, 2011 ; El Fakiri et al, 2008 ; Gary et al, 2009 ; Jansen et al, 2007 ), interventions using patients' native language(s) (Choi & Rush, 2012 ; Piñeiro et al, 2020 ) and bilingual nurses (Bachhuber et al, 2017 ; Brown et al, 2011 ; Choi & Rush, 2012 ; Weiler & Tirrell, 2007 ). Traditional beliefs in relation to medical practice were also acknowledged (Choi & Rush, 2012 ), and culturally appropriate foods were recommended (Brown et al, 2011 ; Choi & Rush, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Included studies also showed that brief interventions can overcome barriers posed by time commitments. Numerous studies outlined brief intervention resources and strategies including clinical decision support tools (Bachhuber et al, 2017 ), brief motivational interviewing techniques (Mertens et al, 2014 ), brief advice interventions (Piñeiro et al, 2020 ) and short questionnaires (Waller et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, there are patient-level factors relevant to implementation. Patients may be less likely to receive SBIRT depending on demographics (e.g., age, sex) or presence of other health problems (Bachhuber et al, 2017;Hodgson et al, 2016). Patients may feel stigma or discomfort in disclosing substance use or having it documented in the EHR (McNeely et al, 2018;Rahm et al, 2015;Spear, Shedlin, Gilberti, Fiellin, & McNeely, 2016).…”
Section: Barriers and Facilitators To Sbirt Implementationmentioning
confidence: 99%
“…Even less is known about implementation needs in other settings. Several studies have indicated that there may be important interactions between the patient and provider that affect SBIRT implementation (Bachhuber et al, 2017;Hodgson et al, 2016). The patient perspective has not been well documented in SBIRT studies.…”
Section: Sbirt Implementationmentioning
confidence: 99%
“…Previous efforts to implement a CDSS have had an inconsistent impact on sex and gender disparities. Integration of a CDSS into the electronic health record of an internal medicine practice did not result in equitable practice, as female patients were less likely to be screened for alcohol use compared to men, although they were not less likely to receive a brief intervention if they screened positive [51]. Another study found that implementation of a performance measure and clinical decision support tool enhanced sex disparities, such that implementation of the performance measure led to a greater increase in rates of brief intervention for men [24].…”
Section: Introductionmentioning
confidence: 99%